Tanjung Lesung Special Economic Zone: Expectation and Reality - Moh. Ilham A Hamudy; M. Saidi Rifki (Policy & Governance Review, 2021)
Many countries have developed Special Economic Zones (SEZ) to spur economic growth. In Indonesia, SEZs have been around for more than a decade. However, the existing SEZs have not yielded the expected results. Likewise with the Tanjung Lesung Tourism SEZ, which is still facing major obstacles in its development. Studies related to the dimensions of the SEZ policy have not been fully carried out, specifically those related to local government involvement. This study aimed to analyze government policy in supporting the development of SEZ, particularly in Tanjung Lesung. This study used a descriptive method with a qualitative approach. This study showed the many obstacles faced for the development of the Tanjung Kelayang SEZ, both of which stem from the weak commitment of the parties involved. Their attitude of blaming each other needs to be changed with the teamwork spirit of working together and creating synergy. Each party seems to wait for each other to make the first move. The limited resources and capabilities caused the policy implementation to come to a halt. The role of the Area Council (Dewan Kawasan) needs to be further optimized to solve problems at the local level. With better information, the central government, through the Directorate General of Territorial Administration Development, Ministry of Home Affairs, can play a more pivotal role in providing strategic considerations in driving the progress of SEZ.